2023
DOI: 10.1186/s12872-023-03093-2
|View full text |Cite
|
Sign up to set email alerts
|

Vascular dysfunction and body mass index in African adults with HIV

Abstract: Background Impaired vascular compliance is common among persons with HIV (PWH) and a risk factor for cardiovascular disease (CVD), though many studies documenting this are from regions with a high prevalence of overweight and obesity. The prevalence and characteristics of impaired vascular compliance among PWH with low body mass index (BMI) is not well described, particularly in sub-Saharan Africa (SSA) where the majority of PWH live, a low BMI is more common, and the burden of CVD is rising. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…HIV infection is a well studied immune system disorder. Vascular dysfunction and hypertension are common in people with HIV (PWH) and have been the focus of recent research [ 70 , 71 ]. While various factors contribute to cardiovascular disease in PWH, the relationship between HIV and salt sensitivity has emerged as an intriguing topic.…”
Section: Targeting Epithelial Sodium Channel In Specific Patient Groupsmentioning
confidence: 99%
“…HIV infection is a well studied immune system disorder. Vascular dysfunction and hypertension are common in people with HIV (PWH) and have been the focus of recent research [ 70 , 71 ]. While various factors contribute to cardiovascular disease in PWH, the relationship between HIV and salt sensitivity has emerged as an intriguing topic.…”
Section: Targeting Epithelial Sodium Channel In Specific Patient Groupsmentioning
confidence: 99%
“…In the Rakai Community Cohort Study in South-Central Uganda (63% female), obesity was also linked to increased odds of certain cardiovascular risk factors, such as hypertension (OR ¼ 2.31, 95% CI: 1.35-3.96) among PWH [33]. With respect to other cardiovascular risk factors, in a sub-Saharan African cohort, Kaluba et al showed that PWH who were overweight had impaired vascular function, assessed through the carotid femoral augmentation index, vs. normal-weight participants after controlling for factors such as sex, age, and blood pressure [34]. However, they also found that other indices of vascular compliance, such as carotid-femoral and carotid-radial pulse wave velocity, did not significantly differ between PWH who were underweight vs. overweight [34].…”
Section: Adverse Complications Associated With Obesity Among People W...mentioning
confidence: 99%
“…With respect to other cardiovascular risk factors, in a sub-Saharan African cohort, Kaluba et al showed that PWH who were overweight had impaired vascular function, assessed through the carotid femoral augmentation index, vs. normal-weight participants after controlling for factors such as sex, age, and blood pressure [34]. However, they also found that other indices of vascular compliance, such as carotid-femoral and carotid-radial pulse wave velocity, did not significantly differ between PWH who were underweight vs. overweight [34]. Additionally, using cross-sectional data from a US-based cohort (73% male and 44% Black), Buendia et al found that participants with overweight and obesity were at higher odds of having high total cholesterol or triglycerides (41% and 30%, respectively) [35].…”
Section: Adverse Complications Associated With Obesity Among People W...mentioning
confidence: 99%
See 1 more Smart Citation